Is gibbon ape leukaemia virus still a threat? - Brown, Katherine; Tarlinton, Rachael E. (Blackwell, 2016)
In the late 1960s and early 1970s, an outbreak of lymphoma and leukaemia in gibbons (Hylobatidae), attributed to the retrovirus gibbon ape leukaemia virus (GALV), was widely reported in the literature. The virus was identified in captive gibbon colonies in Thailand, the USA and Bermuda.The virus is a known cell culture contaminant and, in particular, research into HIV can be impeded by expression of GALV particles in HIV permissive cell lines.In this review, we bring together published work, laboratory records from early GALV research, correspondence about the transportation of gibbons during the 1960s and 1970s, phylogenetic analyses, laboratory screening and zoological records for the first time, to discover more about the origin and transmission of GALV. Based on this evidence, we suggest that GALV may have been transmitted to gibbons as an iatrogenic event and was never widespread. Instead, all infected gibbons were probably transported from the site of the original outbreak, housed with gibbons from this site or infected with material derived from gibbons from this site. We also propose that GALV is not an ongoing pathogen of captive gibbons.